INTERAKSI SOSIAL ANAK PUTUS SEKOLAH DENGAN YANG MASIH SEKOLAH DI DUSUN TIANG AJI MENJALIN - Halim, Damianus; Imran, Imran; Budjang, Gusti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out how the social interaction of school dropouts with children who are still in school in the Tiang Aji Menjalin hamlet. In this study the method used is descriptive method with data collection techniques namely observation techniques, interviews and documentary studies. Sources of data in this study drop out of school children and children who are still in school and the head of the Tiang Aji Menjalin Hamlet. The results showed that: 1) The imitation factor that led to social interaction between school dropouts and children who were still in school was more imitating the behavior of their negative social group friends, such as consuming alcohol and smoking if they got along. 2) Factors suggesting that the social interaction of school dropouts with children still attending school is more influential given to school dropouts for children who are still in school because the majority of their associate friends are school dropouts, the negative influence of school dropouts influences attitudes and behavior of children who are still in school. Keywords: Social Interaction, Dropout Children School and Children Still   School.